MECHANISMS OF ANEMIA FORMATION IN COLORECTAL CANCER, ITS CLINICAL AND LABORATORY CHARACTERISTICS - Андрияка, Артем (SWorldJournal, 2021)
The clinical-hematological features of anemia in oncological diseases are described in the article. The mechanisms of anemia formation and features of iron metabolism at oncological patient are discussed. Colorectal cancer is an extremely urgent issue in